Application of quality by design (qbd) to reformulation of chewable tablets (2013)
This research work illustrates the implementation of Quality by Design (QbD) principles into pharmaceutical industry. The manufacture of chewable tablets was chosen as case study. In this way, product formulation and preparation procedure were reformulated. The starting point was the definition of the product quality profile from which the critical quality attributes were identified. Also, the impact and the criticality of each stage of manufacture for the product were examined regarding to their influence in achieving the critical quality attributes. Risk assessment was made for critical manufacture stages and considering the results, mitigation strategies were proposed and implemented. This leads to a formulation satisfying the requirements for the organoleptic properties like the 25% reduction in the production time.